GAMBARAN KUALITAS TIDUR PASIEN HIV/AID DENGAN GANGGUAN NEUROPATI PERIFER DI RSUP Dr. M. DJAMIL PADANG - Milzam Radifan Akridhol; Yuri Haiga; Nilas Warlem (Yayasan Nusantara Hasana Berdikari, 2025)
Human Immunodeficiency Virus is a type of virus that infects human immunity, namely white blood cells, which results in a decrease in the human immune system, causing AIDS. Acquired Immunodeficiency Syndrom is a group of disease symptoms that arise due to a decrease in the immune system due to HIV infection. The current effective therapy for HIV/AIDS patients is antiretroviral. Efavirenz is an antiretroviral drug that often causes neuropsychiatric side effects, one of which is sleep disturbance. To determine the description of sleep quality in HIV / AIDS patients with Peripheral Neuropathy Disorders at Dr. M. Djamil Padang Hospital. The scope of this research is neurology and internal medicine. This study was conducted at Dr. M. Djamil Padang Hospital in March 2024 to November 2024.This study was conducted using a categorical descriptive method. using primary data. The target population of this study were all HIV/AIDS-infected patients with Peripheral Neuropathy Disorders at the VCT Polyclinic of Dr. M Djamil Padang Hospital who were given the PSQI questionnaire. The number of samples in this study were 63 with total sampling technique. Univariate data analysis is presented in the form of frequency distribution. Data processing using the computerized SPSS program IBM version 25. The results of this study showed that most HIV/AIDS patients aged 26-35 years were 30 patients (47.6%). The most gender was male patients, 55 patients (87.3%). The most common occupation was self- employed, namely 22 patients (34.9%). The number of HIV/AIDS patients with sleep quality disorders was 60 patients (95.2%), and many patients used efavirenz, 57 patients (90.5%). HIV/AIDS patients were mostly aged 26-35 years, male, self-employed, had sleep disturbances and used efavirenz.